2014
DOI: 10.1088/0004-6256/148/3/43
|View full text |Cite
|
Sign up to set email alerts
|

Time Elements for Enhanced Performance of the Dromo Orbit Propagator

Abstract: We propose two time elements for the orbit propagator named Dromo. One is linear and the other constant with respect to the independent variable, which coincides with the osculating true anomaly in the Keplerian motion. They are defined from a generalized Kepler's equation written for negative values of the total energy and, unlike the few existing time elements of this kind, are free of singularities. To our knowledge it is the first time that a constant time element is associated with a second-order Sundman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 31 publications
(64 reference statements)
0
42
0
Order By: Relevance
“…One fundamental aspect of the analytical procedure employed in the article is the use of a convenient orbital motion formulation to ease the analytical treatment as much as possible. The so called "Dromo" formulation initially introduced by Peláez et al (2007) and complemented by other authors [see Baù et al (2013); Baù and Bombardelli (2014)] is chosen here due to its suitability when dealing with a constant radial thrust problem. This is because it is intrinsically based on a local vertical-local horizontal orbiting frame where a purely radial acceleration component appears as a simple perturbing term in the equations of motions.…”
Section: Introductionmentioning
confidence: 99%
“…One fundamental aspect of the analytical procedure employed in the article is the use of a convenient orbital motion formulation to ease the analytical treatment as much as possible. The so called "Dromo" formulation initially introduced by Peláez et al (2007) and complemented by other authors [see Baù et al (2013); Baù and Bombardelli (2014)] is chosen here due to its suitability when dealing with a constant radial thrust problem. This is because it is intrinsically based on a local vertical-local horizontal orbiting frame where a purely radial acceleration component appears as a simple perturbing term in the equations of motions.…”
Section: Introductionmentioning
confidence: 99%
“…Dromo features a second order Sundman transformation that introduces the ideal anomaly, which behaves as the independent variable. Later studies defined a time element to improve the integration of the time transformation Baù and Bombardelli, 2014). The formulation has been progressively improved and the latest version is that by Urrutxua et al (2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Numerical explorations by Fukushima (2005) yielded two important conclusions about the use of time elements (in the context of the KS regularization): first, the error growth rate is reduced from quadratic to linear; second, it removes the periodic components of the error in unperturbed problems. A detailed review on time elements can be found in the work by Baù and Bombardelli (2014), where they also attached a constant and a linear time element to the set of Dromo elements.…”
Section: Time Elementsmentioning
confidence: 99%
“…In unperturbed motion, the fictitious time collapses to the true anomaly measured from the departure point of the ideal frame. The method was then improved by the introduction of a perturbing potential [5] and time elements [4].…”
Section: Dromo Formulationsmentioning
confidence: 99%
“…With a linear time element, the rate of growth of the global truncation error behaves linearly instead, but the local truncation error is bigger. Thus, it is advised to use the latter in long-term integrations involving several millions orbits [4,76].…”
Section: Numerical Implications Of Regularizationsmentioning
confidence: 99%